Efficacy of Modified Ban Xia Xie Xin Decoction on Functional Dyspepsia of Cold and Heat in Complexity Syndrome: A Randomized Controlled Trial - Zhao, Luqing (Hindawi Publishing Corporation, 2013)
Background. Chinese herbal medicine (CHM) has been used in China and elsewhere to treat patients with functional dyspepsia (FD). However, controlled studies supporting the efficacy of such treatment are lacking. Objective. To assess the efficacy and safety of modified Ban xia xie xin decoction in patients with FD of cold and heat in complexity syndrome. Methods. We performed a randomized, double-blind, placebo-controlled trial involving patients from five centers. Patients with FD of cold and heat in complexity syndrome (n = 101) were randomly assigned to groups given either CHM modified Ban Xia Xie Xin decoction or placebo in a 2 : 1 ratio. Herbal or placebo granules were dissolved in 300 mL of boiled water cooled to 70°C. Patients in both groups were administered 150 mL (50°C) twice daily. The trial included a 4-week treatment period and a 4-week followup period. The primary outcomes were dyspepsia symptom scores, measured by the total dyspepsia symptom scale and the single dyspepsia symptom scale at weeks 0, 1, 2, 3, 4, and 8. Results. Compared with patients in the placebo group, patients in the CHM group showed significant improvements according to the total and single dyspepsia symptom scores obtained from patients (P < 0.01) and investigators (P < 0.01). Conclusions. CHM modified Ban Xia Xie Xin decoction appears to offer symptomatic improvement in patients with FD of cold and heat in complexity syndrome. Trial Registration. Chinese Clinical Trial Registry (ChiCTR): ChiCTR-TRC-10001074.